1990
DOI: 10.1128/jvi.64.2.774-783.1990
|View full text |Cite
|
Sign up to set email alerts
|

cis elements and trans-acting factors involved in dimer formation of murine leukemia virus RNA

Abstract: The genetic material of all retroviruses examined so far consists of two identical RNA molecules joined at their 5' ends by the dimer linkage structure (DLS). Since the precise location of the DLS as well as the mechanism and role(s) of RNA dimerization remain unclear, we analyzed the dimerization process of Moloney murine leukemia virus (MoMuLV) genomic RNA. For this purpose we derived an in vitro model for RNA dimerization. By using this model, murine leukemia virus RNA was shown to form dimeric molecules. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
123
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(130 citation statements)
references
References 39 publications
6
123
1
Order By: Relevance
“…Non-templated assembly involves the formation of a larger structure by individual components without any influence from external forces. Included in the non-templated category are ligation, chemical conjugation, covalent linkages, loop/loop interactions of RNAs and the formation of macromolecules by structural interaction in the formation of multimers [12,54,[135][136][137][138]. The use of bacteriophage phi29 pRNA as a building block for the construction of micrometre-sized RNA arrays for potential tissue and wound repair has been reported [11].…”
Section: Principles and Approaches In Engineering Rna For Conjugationmentioning
confidence: 99%
“…Non-templated assembly involves the formation of a larger structure by individual components without any influence from external forces. Included in the non-templated category are ligation, chemical conjugation, covalent linkages, loop/loop interactions of RNAs and the formation of macromolecules by structural interaction in the formation of multimers [12,54,[135][136][137][138]. The use of bacteriophage phi29 pRNA as a building block for the construction of micrometre-sized RNA arrays for potential tissue and wound repair has been reported [11].…”
Section: Principles and Approaches In Engineering Rna For Conjugationmentioning
confidence: 99%
“…The interactions between NC protein and the genomic RNA in alpha-(RSV) and gamma-RV (MoMuLV) virions were initially examined using UV light at 252 nm for cross-linking since this approach allows the specific spatial relationship of certain amino acids and RNA bases to be characterized (see Burd and Dreyfuss, 1994). Results showed that NC was by far the major protein tightly bound to the genomic 70S RNA in the nucleocapsid (Darlix and Spahr, 1985;Meric et al, 1984;Prats et al, 1990;Tanchou et al, 1995). But these results were obscured and a matter of intense debate because MAp19 protein of RSV and pp12 protein of MoMuLV were originally reported to be the viral proteins tightly linked to the genome in virions (Darlix and Spahr, 1982;Sen et al, 1977).…”
Section: Characterization Of Nc Protein As the Major Viral Rna Ligandmentioning
confidence: 99%
“…The NC cross-linked RNA fragments were recovered and upon sequencing it was found that NC tightly binds a small number of genomic RNA sites rich in U and G residues, located in the multifunctional 5 untranslated leader region (5 UTR) (Dannull et al, 1994;Darlix and Spahr, 1982;Meric et al, 1984;Tanchou et al, 1995). This was of special interest since these sites are close to the dimer linkage structure (DLS) (Darlix and Spahr, 1982;Prats et al, 1990) that holds together the two genomic RNA in the virion nucleocapsid (Murti et al, 1981), and the DLS is part of the packaging psi signal (Pugatsch and Stacey, 1983). These findings suggested that NC interaction with high affinity sites presents in the 5 leader region, close to the DLS, might be required for the selective packaging of the genomic RNA during virus morphogenesis (Aldovini and Young, 1990;Lever et al, 1989).…”
Section: Characterization Of Nc Protein As the Major Viral Rna Ligandmentioning
confidence: 99%
See 1 more Smart Citation
“…PR-defective particles are stable in conditions that disrupt mature virions (Stewart et al118 and references therein) which suggests that one function of PR may be to facilitate disassembly of virus particles after uptake into a cell. The involvement of processing in RNA dimerization may be important in viral replication, since a role for the dimeric RNP complex in reverse transcription has been postulated (Prats et al96 and references therein). Moreover, it is apparent that replicative enzymes such as RT are activated by proteolytic removal of inhibitory flanking domains (Le Grice et al 73 and Stewart et al 118, and references therein).…”
mentioning
confidence: 99%